KONSEP KETUHANAN DALAM LONTAR GONG BESI - I Made Arya (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2018)
Lontar Gong Besi is one of the referens of Hindus especially mazab shiva. Lontar iswritten a mahakawi, as well as the rajakerta Hindu community in Bali, named Mpu Kuturan.Many teachings can be learned from reading this ejection. Careful scrutiny, descriptions for thedescription of the eons of Gong Gong found, the Concept of Godhead, the omnipotence of BhataraDalem, Hyang Parameswara (ista Dewata) saktiya Siwa. The omnipotence of the soul becomesthe source of creation (utpati), the maintenance (stiti), and the power restores to its origin (pralina).In the tradition of Hindu community life in Bali, the concept of the lontar cadence of Gong Wesiis manifested in the form of worship, both at the village level of pakraman, and at the familylevel. Sanggah/Studio as linggih (stana) Hyang Tunggal, Hyang Atma in Kamulan Tengen (rightroom) is Bapanta, Paratma in Kemulan Kiwa (left room) is Ibunta, and Hyang Siwatma inKemulan Madya (living room) is raganta. Susunatma is meme, father and ragane go back toDalem become Hyang Tunggal. Conclusion, the concept of divinity in ejection Gong Wesi in thereligious social life of Hindu society in Bali.